Efficacy of transdermal glyceryl trinitrate in the treatment of chronic stable angina pectoris. Issue 6 (June 1985) - James, M A; Walker, P R; Papouchado, M; Wilkinson, P R
Abstract : A study was carried out to assess the efficacy of a new transdermal preparation of glyceryl trinitrate (Transiderm-Nitro 5) in the 24 hour prophylaxis of angina and to determine the duration of effect of a single patch application. Twelve men with chronic stable angina were studied in a randomised, placebo controlled, double blind trial. By serial treadmill exercise testing a therapeutic effect was shown at three hours; the exercise time to angina and to 1 mm ST segment depression and the total exercise time were all significantly increased. At 24, 48, and 72 hours, however, no therapeutic effect was observed. Recent studies have shown a similar lack of effect at 24 hours for various forms of transdermal delivery systems. It is suggested that this lack of effect is due to the rapid onset of tolerance probably as a result of the constancy of blood concentrations obtained by this method of administration.